Structural Modifications of the Small Intestine of the African Giant Rat (Cricetomys gambianus, Waterhouse): Implications for Dietary demands and Improved Domestication - Samuel Gbadebo Olukole; Olatunji-Akioye Adenike Olusola; Oluwaseyi Oyeniyi Owolabi; Oke Bankole Olusiji (Turkish Journal of Agriculture: Food Science and Technology)
The African giant rat (Cricetomys gambianus, Waterhouse) is a wild rodent in sub-Saharan Africa widely hunted as popular meat delicacy. Domestication of this rat has been poor, probably due to nutrition among other factors. Developmental studies of the duodenum, jejunum and ileum as well as investigations of diet-based structural modifications of the small intestine were carried out in the rats using neonates, juveniles and adults with the aim of providing useful research information which could lead to improved domestication. The mean body weights of the animals were 39.67±1.45 g, 225.00±25.00 g and 742.90±62.13 g, respectively for the neonate, juvenile and adult rats. Significant differences were also observed in the villus height, villus width and crypt depth between the neonates and juveniles, unlike between juvenile and adult rats. These changes in intestinal morphology between the neonate and juvenile rats could be a measure of the neonates’ adaptation to shifts from digestion of maternal milk to the consumption of solid and semisolid forages. Respectively for neonates, juvenile and adult rats, 188%, 228% and 30% increases in villus height for the duodenum, jejunum and ileum respectively, were observed. This is suggestive of larger surface area of the small intestine for digestion and absorption. This study elucidates the structural modifications of the small intestine which can be applied to dietary modifications in response to age in an effort to achieve a more successful domestication of the animal.